2011
DOI: 10.1542/peds.2011-0215
|View full text |Cite
|
Sign up to set email alerts
|

Child Passenger Safety

Abstract: Despite significant reductions in the number of children killed in motor vehicle crashes over the past decade, crashes continue to be the leading cause of death for children 4 years and older. Therefore, the American Academy of Pediatrics continues to recommend inclusion of child passenger safety anticipatory guidance at every health-supervision visit. This technical report provides a summary of the evidence in support of 5 recommendations for best practices to optimize safety in passenger vehicles for childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(32 citation statements)
references
References 78 publications
1
31
0
Order By: Relevance
“…A 2012 survey in the large city of Shanghai found that only 5.1% of children under the age of 7 were restrained while traveling in a car [3]. Our 2012 observational survey in the middle-sized city (and therefore less influenced by international trends) of Shantou found that fewer than 1% of children were restrained [4].Correct use of a child safety restraint in the proper seating position can reduce the risk of fatality by up to 71% and the risk of serious injury up to 67% [5]. With rapidly increased motorization in China, there is a great need to develop and test intervention strategies that could effectively increase child safety restraint usage in China [6], since Chinese parenting customs coupled with low safety awareness could serve as barriers to CSS use.…”
Section: Introductionmentioning
confidence: 75%
“…A 2012 survey in the large city of Shanghai found that only 5.1% of children under the age of 7 were restrained while traveling in a car [3]. Our 2012 observational survey in the middle-sized city (and therefore less influenced by international trends) of Shantou found that fewer than 1% of children were restrained [4].Correct use of a child safety restraint in the proper seating position can reduce the risk of fatality by up to 71% and the risk of serious injury up to 67% [5]. With rapidly increased motorization in China, there is a great need to develop and test intervention strategies that could effectively increase child safety restraint usage in China [6], since Chinese parenting customs coupled with low safety awareness could serve as barriers to CSS use.…”
Section: Introductionmentioning
confidence: 75%
“…This previous study was conducted in 2010, prior to the American Academy of Pediatrics Child Passenger Safety Policy Statement and Technical Report in 2011 [1,2], yet even with these new guidelines, inconsistent booster seat use in carpooling still exists. Even among those who typically use booster seats, only 71.7% reported always using a booster seat for their own child when carpooling other children, and only 67.5% reported always asking others to have their child ride in a booster seat when others are driving them.…”
Section: Discussionmentioning
confidence: 99%
“…Suboptimal compliance with child restraint system (CRS) recommendations [1,2] can increase risk for injury or death if a crash does occur [3,4,5]. After children grow out of harness systems, booster seats help to adequately restrain children in the years they are not yet ready for the seat belts outfitted in vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…2,6,13,14,19 While it has been observed that upwards of 70-90% of 4-7 year-olds are using some sort of restraint, many in this age group are not using the appropriate restraint type. 7,22,26 Even when children are riding in an age-appropriate BPB seat, an estimated 64% are using the seat incorrectly. 25 The seating position of the pediatric occupant also plays a large role in the child's risk of injury.…”
Section: Introductionmentioning
confidence: 99%
“…When riding in the front seat, the child is at a greater risk for severe injury or death compared to a child seated in the second row. 7,9,14,17,27 Although many states recommend that children age 13 and under ride in the second row, the NHTSA reports 8% of 4-7 year-old passengers were riding in the front passenger seat in 2011. 26 The consequences of pediatric lower extremity interactions with front row features such as the dashboard and airbags are not well documented.…”
Section: Introductionmentioning
confidence: 99%